Eksplorasi Pesan Hadits di Era Digital: Studi pada Media Film, Animasi, dan Sinetron - Nazmi, Khairin; Faza, Asrar Mabrur; Syahriza, Rahmi (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
The 21st century is marked by rapid advancements in globalization, information technology, and communication, which have brought significant changes to the world of education. Technology also plays a role in renewing our understanding of learning, which has now evolved from simply delivering information to guiding exploration of social and cultural aspects. This study aims to explore multimedia-based Hadith research, particularly in relation to film and animation media, examining the reception of Hadith in a modern context. The research conducted is of a literature-based type, involving both primary and secondary data collection. Primary data is gathered through films, television shows, and animations focusing on mapping multimedia-based Hadith research, while secondary data is drawn from relevant literature. Data collection techniques include document study and content analysis, enabling the exploration of social and cultural messages within the media. The findings indicate that television series and animated films, such as Nussa Rara, Culapculip, and Omar Hana, have become popular platforms for spreading Hadith messages, particularly on YouTube channels. Meanwhile, the phenomenon of feature films, such as Ipar Adalah Maut, further proves that Hadith remains relevant and accessible in various media formats. Thus, multimedia-based Hadith research plays an important role in expanding public knowledge and understanding of Hadith in a modern context.